Disentangling crossing fibers with advanced dMRI methods reveals bundle-specific degeneration across the visual system in asymmetric glaucoma - Daniela Coutiño; Judith Guerrero-Zavala; César Arturo Domínguez-Frausto; Marlene García-Guillén; Ricardo Coronado-Leija; Alonso Ramírez-Manzanares; Erick Hernández-Gutiérrez; Maxime Descoteaux; Martin Ayala; Mariana Badillo; Luis Concha (PLoS ONE, 2026)
Diffusion magnetic resonance imaging (dMRI) is a non-invasive neuroimaging technique that enables in vivo assessment of white matter microstructure and is highly sensitive to tissue alterations associated with disease. Although substantial evidence links diffusion-derived metrics to underlying white matter tissue properties, the presence of complex within-voxel axonal configurations complicates their biological interpretation. Several methods have been proposed to assess diffusion properties of individual crossing axonal populations, but their validation and clinical applicability remain limited. Glaucoma, the second leading cause of blindness worldwide, is characterized by progressive loss of retinal ganglion cells and axonal damage in the optic nerve, leading to degeneration along the entire visual pathway. This degeneration includes secondary effects on fiber crossings within the optic chiasm, which are challenging to characterize with conventional diffusion methods. Here, we evaluated whether advanced diffusion metrics can detect microstructural alterations in these complex white matter configurations and whether these measures correlate with clinical markers of glaucoma severity. In this study, we evaluated 31 patients with asymmetric glaucoma and 31 healthy controls using advanced diffusion magnetic resonance imaging methods, including Diffusion Tensor Imaging, Constrained Spherical Deconvolution, multi-tensor fit via Multi-Resolution Discrete Search method, and Fixel-Based Analysis. We found significant differences of diffusion metrics in white matter tracts of the visual system, including the optic nerve, optic chiasm, optic tracts, and optic radiations. Moreover, diffusion metrics correlated with clinical ophthalmological parameters such as cup-to-disc ratio, visual field mean deviation, and retinal nerve fiber layer thickness. These findings support the use of advanced diffusion magnetic resonance imaging models as sensitive tools for detecting Wallerian degeneration and resolving complex white matter architecture in the human visual pathway, and demonstrate their utility to study other fiber-crossing regions throughout the brain.